The Compensatory Protective Effects of Social Support at Work in Presenteeism During the Coronavirus Disease Pandemic - Chen, Jia Wun; Lu, Luo; Cooper, Cary L. (Frontiers in Psychology, 2021)
The present study investigated the lasting effects of sickness presenteeism on well-being and innovative job performance in the demanding Chinese work context compounded with the precarities of the post pandemic business environment. Adopting the conservation of resources (COR) theory perspective, especially its proposition of compensation of resources, we incorporated social resources at work (supervisory support and collegial support) as joint moderators in the presenteeism-outcomes relationship. We employed a panel design in which all variables were measured twice with six months in between. Data were obtained from 323 Chinese employees working in diverse industries in Taiwan. We found that after controlling for the baseline level of well-being, presenteeism did not have a lasting effect on employees’ exhaustion. However, presenteeism did have a negative lasting effect on employees’ innovative behavior 6 months later. Moreover, we found a significant 3-way interaction of presenteeism, supervisory support and collegial support on employees’ innovative job performance, after controlling for the baseline level of performance. Specifically, when working under illness, employees displayed the best innovative performance with high levels of both supervisory and collegial support, the worst performance with both support being low, and the intermediate when any one of the support being high. This can be taken as the preliminary evidence to support the COR proposition of resource caravans, showing that supervisory support and collegial support compensated for each other as critical resources in alleviating the impact of working under sickness on employees’ innovative performance. Theoretical implications of the findings are discussed, taking into account the macro-cultural context of the East Asian Confucian societies. We also reflected on the managerial implications of the lasting damages of sickness presenteeism and benefits of mobilizing social resources on employees’ well-being and performance.